2014
DOI: 10.1039/c4sm00587b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of three-dimensional open structures using patchy colloidal particles

Abstract: Open structures can display a number of unusual properties, including a negative Poisson's ratio, negative thermal expansion, and holographic elasticity, and have many interesting applications in engineering. However, it is a grand challenge to self-assemble open structures at the colloidal scale, where short-range interactions and low coordination number can leave them mechanically unstable. In this paper we discuss the self-assembly of open structures using triblock Janus particles, which have two large attr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…24,59,61,62 Additionally, our model exhibits qualitatively similar phase behavior to previous thermodynamic studies on equilibrium triblock Janus colloids. 42,43,55,63 A more complete discussion of this patchy potential and its functional form can be found in the Supporting Information. Below we list the key features of the anisotropic interaction potential, which drives the formation of the kagome lattice:…”
Section: Model and Analysismentioning
confidence: 99%
“…24,59,61,62 Additionally, our model exhibits qualitatively similar phase behavior to previous thermodynamic studies on equilibrium triblock Janus colloids. 42,43,55,63 A more complete discussion of this patchy potential and its functional form can be found in the Supporting Information. Below we list the key features of the anisotropic interaction potential, which drives the formation of the kagome lattice:…”
Section: Model and Analysismentioning
confidence: 99%
“…the patch angular width, was particularly investigated and it was shown that, when this value is high enough to enable one patch to interact simultaneously with the patches of two neighboring particles, ring structures may be promoted leading to a two-dimensional Kagome lattice [199]. It has also been shown theoretically that triblock Janus parti-cles, which have two large attractive patches separated by a repulsive band, can form a 3D pyrochlore lattice [200]. Romano and Sciortino have further demonstrated by performing Monte Carlo simulations that a rational design of the shape and the symmetry of the two patches can drive the patchy particles to crystallize in a single morphology by eliminating the undesired polymorphs [201].…”
Section: A Numerical Self-assembly Of Patchy Hard Spheresmentioning
confidence: 99%
“…For classes of competing structures that contain free parameters, the values of those parameters are determined by minimizing the chemical potential (using GAMS) under the optimized pair potential (for details see appendix of ref. 25). Any structures that are revealed by this calculation to be more stable than the target lattice are added to the competing pool to be used in the next iteration of the pair potential optimization.…”
Section: B Competing Pool Selectionmentioning
confidence: 99%